Estudo das propriedades elétricas e de sensoriamento de H2 em heteroestruturas bidimensionais de grafeno - Alisson Ronieri Cadore (2017)
Graphene, a two-dimensional (2D) material composed only by carbon atoms, has been widely studied due to its electrical, mechanical and optical properties. Recently, the combination of graphene with others 2D materials (van der Waals heterostructures) leaded to improvements of the device quality allowing observation of novel optical and quantum phenomena with potential for technological applications. However, implementing graphene devices in industry is challenging and needs preparation of high quality nanostructures able to operate at desired temperatures and environments. In this thesis we fabricate 2D heterostructures formed by graphene and hexagonal boron nitride (hBN) and we study their electrical properties operating as transistors and selective gas sensors. In our first approach, we show the influence of temperature on the performance of graphene/hBN field effect transistors. Essentially, we observe an anomalous behavior of the resistance of graphene/hBN device at temperatures larger than T = 100°C and we describe how to avoid such problem. Latter, we present our study on selective detection of H2. We investigate the influence of the metallic contacts on the ambipolar conduction of graphene devices, and how heterojunctions formed at graphene/contact interfaces can be modulated via interaction with molecular hydrogen. Such modulation endows to a systematic and reproducible modification of the electronic properties of the graphene devices and can be used as a selective way of detecting molecular hydrogen.